2018
DOI: 10.1128/jvi.01760-17
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Chronic Lymphocyte Activation following Interferon Alpha Blockade during the Acute Phase of Simian Immunodeficiency Virus Infection in Rhesus Macaques

Abstract: Pathogenic human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection of humans and rhesus macaques (RMs) induces persistently high production of type I interferon (IFN-I), which is thought to contribute to disease progression. To elucidate the specific role of interferon alpha (IFN-α) in SIV pathogenesis, 12 RMs were treated prior to intravenous (i.v.) SIV infection with a high or a low dose of an antibody (AGS-009) that neutralizes most IFN-α subtypes and were compared with six mock-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…In addition, because the 3x weekly ART group had a generally higher VL compared to animals that received twice weekly IFN-1ant ( Fig 4 ), there is likely a threshold where any measurable effect of the antagonist added to the effect of ART is influenced by the viremia at the time antagonist treatment is initiated. Our findings possibly reinforces the importance of timing on the outcome of IFN-I signaling blockade as administration of IFN-I antagonist [ 5 ] and more recently anti-IFN antibody treatment [ 30 ] in SIV infected macaques was shown to reduce T cell activation. The observations in our study also differ from observations made in prior studies on IFN-I blockade in chronically HIV-infected humanized mice which showed reduced expression of ISGs along with enhanced viral suppression and reduced T cell activation [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, because the 3x weekly ART group had a generally higher VL compared to animals that received twice weekly IFN-1ant ( Fig 4 ), there is likely a threshold where any measurable effect of the antagonist added to the effect of ART is influenced by the viremia at the time antagonist treatment is initiated. Our findings possibly reinforces the importance of timing on the outcome of IFN-I signaling blockade as administration of IFN-I antagonist [ 5 ] and more recently anti-IFN antibody treatment [ 30 ] in SIV infected macaques was shown to reduce T cell activation. The observations in our study also differ from observations made in prior studies on IFN-I blockade in chronically HIV-infected humanized mice which showed reduced expression of ISGs along with enhanced viral suppression and reduced T cell activation [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…In fact, IFNAR blockade during chronic HIV-1 infection in humanized mice restored immune function, leading to better HIV-1 control [31,32]. Neutralization of (most) IFNα subtypes in SIV-infected rhesus macaques prior to infection increased viral loads as expected, but also decreased subsequent immune activation profiles [24]. By contrast, blockade of IFN-I signaling in chronic SIVtreated and untreated rhesus macaques decreased inflammation profiles associated with ISGs but did not reverse T cell exhaustion or activation [33].…”
Section: Introductionmentioning
confidence: 61%
“…Genetic ablation of IFNAR resulted in higher Friend retrovirus replication in mice co-infected with lactate-dehydrogenase elevating virus, a potent IFN-I inducer [22]. Moreover, IFNAR blockade increased SIV replication in rhesus macaques [23,24]. Administration of IFNα2 decreased retrovirus replication in mice, monkeys and humans [3,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Sample collection and tissue processing. Longitudinal collection and processing of blood, fine needle aspirates (FNA), or lymph node and rectal biopsy specimens were performed as previously described (33,34,40,41). Briefly, 2 ml of blood samples was used for complete blood count (CBC), the remaining blood was centrifuged to collect plasma, and then peripheral blood mononuclear cells (PBMCs) were collected over density gradient centrifugation using Ficoll (Gibco, Massachusetts).…”
Section: Methodsmentioning
confidence: 99%